Accuracy of the German income approach in comparison to German DCF valuations. Issue 3 (2nd July 2020) - Reinert, Jan
ABSTRACT: The traditional German Income Approach (GIA) is often criticised for resulting in smooth and stable estimations of value that do not adequately represent market movements. So far, empirical evidence has been scarce. The first part of the analysis consisted of a direct comparison of actual valuations and sale prices according to GIA and DCF models in Germany. The second part of the analysis used hedonic regressions to derive fitted sale prices that could be compared to valuations of held properties in order to assess valuation accuracy on a larger and more homogenous dataset. The Heckman Correction was used to reduce the impact of sample selection bias. The research hypothesis, that GIA valuations and DCF valuations result in equally accurate proxies for market prices, could not be rejected. Both techniques produced on average a comparable amount of valuations within the selected threshold of 15%. This finding suggests that the underlying valuation technique, at least with respect to DCF and GIA, is not able to explain the observed smoothness of German valuation-based indices. Future research should focus on a country comparison of valuation accuracy in order to put the results of this study into perspective.